2022
DOI: 10.1038/s41598-022-05934-0
|View full text |Cite
|
Sign up to set email alerts
|

Vibration analysis of nanobeams subjected to gradient-type heating due to a static magnetic field under the theory of nonlocal elasticity

Abstract: Nanoelectromechanical systems (NEMS) have received great interest from researchers around the world since the advent of nanotechnology and nanoengineering. This can be attributed due to the unique characteristics of NEMS devices and their wide range of applications. Among these applications, nanobeams and nanotubes now have an important role in the design of a variety of NEMS engineering devices. In the current research, the thermoelastic vibration analysis of Euler–Bernoulli nanobeams has been investigated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The theory of nonlocal elasticity has been studied by many researchers Eringen and Edelen (1972), Eringen (1983), Inan and Eringen (1991), Wang and Dhaliwal (1993), Zenkour and Abouelregal (2016), Zhu et al (2017), Sarkar et al (2020) and Othman and Said (2014). Various vital approaches for determining the solutions of the governing equations of problems in thermodynamics, electrohydrodynamics and thermoelasticity have been introduced by Abouelregal and Ahmad (2021) and Ahmad et al (2022).…”
Section: Memorydependent Derivativementioning
confidence: 99%
See 2 more Smart Citations
“…The theory of nonlocal elasticity has been studied by many researchers Eringen and Edelen (1972), Eringen (1983), Inan and Eringen (1991), Wang and Dhaliwal (1993), Zenkour and Abouelregal (2016), Zhu et al (2017), Sarkar et al (2020) and Othman and Said (2014). Various vital approaches for determining the solutions of the governing equations of problems in thermodynamics, electrohydrodynamics and thermoelasticity have been introduced by Abouelregal and Ahmad (2021) and Ahmad et al (2022).…”
Section: Memorydependent Derivativementioning
confidence: 99%
“…For this model, we can consider several kinds of Taylor approximations to recover the previously cited theories. Abouelregal and Ahmad (2021) and Ahmad et al. (2022) have solved different problems applying the 3PHL model.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that the nonlocal nanoscale parameters causes an increase in the natural frequency of transverse vibration of the beam. Applying the nonlocal elasticity theory, Ahmad et al 45 showed the significance of the nonlocal parameter on the nanobeam dynamic response. Laplace transformation was used in the analytical solution.…”
Section: Introductionmentioning
confidence: 99%